Age and VAP Bundle Factors Support the Success of Ventilator Weaning in Patients with Post Evd E.C Hydrocephalus Communica, ME TB BRMC Grade II in the ICU room - Taufindari, Revita Pricilia Ananda Putri; Setioputro, Baskoro (Journal of Nursing Care, 2025)
Ventilator weaning disorder is the inability to adapt to the reduction of mechanical ventilator assistance that can hinder and prolong the weaning process. Meningitis is strictly defined as inflammation of the meninges, while encephalitis is defined as inflammation of the brain. If both are inflamed, the patient experiences meningo encephalitis. Ventilator weaning (or ventilator weaning) is the process of gradually reducing the mechanical respiratory support provided by the ventilator to the patient. Successful weaning is defined as effective spontaneous breathing without any machine support for 24 hours or more. Study was to analyze ventilator weaning in post evd patients e.c communicating hydrocephalus, me tb brmc grade ii in the icu room of prof. Dr. I.g.n.g ngoerah bali hospital. The method used is a quantitative case study method. The data source of this study is primary data that has been interviewed with the patient’s family and also refers to medical record data as secondary data. The results obtained in this study are that the success factor of ventilator weaning is related to the patient’s age. In early adulthood, it is easier to achieve successful ventilator weaning because the body’s immune function, respiratory muscles and lung function are stronger compared to late adulthood. Then, oral hygiene measures will reduce the incidence of vap and avoid oral infections. Because these measures can kill bacterial growth in the oropharynx. The application of the vap bundle for the prevention and control of vap is stated in the regulation of the minister of health (permenkes) of the republic of indonesia number 27 of 2017 concerning guidelines and prevention of infection which includes hand hygiene, bed position 30-45°, oral hygiene, management of oropharyngeal and tracheal secretions, daily sedation assessment, and administration of deep vein thrombosis (dvt) prophylaxis. The conclusion of this study is that age factors and vap bundles can support the success of ventilator weaning in post-evd patients e.c communicated hydrocephalus, me tb brmc grade ii in the icu room of prof. Dr. I.g.n.g. Ngoerah bali hospital